The Role of Organizational Conflict on The Relationship of Organizational Justice and The Performance of Lecturers In Private Universities In Riau Indonesia: - - RAHMAN, ARRAFIQUR; Zulkifli, Norhayah; Bakar, Mohd. Norazwan A. (ADPEBI, 2022)
The study of organizational conflict is a study that needs to receive attention in the ever -changing organizational code in the era of industrial revolution 4.0 today, so this study contributes to the organizational conflict literature that specifically to test the role of organizational conflict on organizational justice and performance. This study was conducted on private universities lecturers in Riau Indonesia region of 298 respondents through stratified proportional random sampling method, using questionnaires and data analysis using SEM PLS. The results of the study found that organizational justice positive and insignificant to performance, organizational justice negative and significant to organizational conflict, organizational conflict negative and significant to performance, and organizational conflict fully mediate the relationship of organizational justice and performance.